2023
DOI: 10.15379/ijmst.v10i3.1718
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Learning of University Students: A Bibliometric Review in Scopus

Vilma Candelaria Yarasca- Quispe,
María Santos Oyola- Canto,
Ana Irene Yarasca- Quispe
et al.

Abstract: A student's ability to structure, monitor and evaluate his or her own learning is known as self-regulated learning and is characterized as a process of self-reflection and action. The present study aimed to conduct a worldwide literature review in Scopus on self-regulated learning of university students during the period 2003-2023. It was a bibliometric analysis that defined the metrics of scientific production. The indicators were obtained from 615 documents chosen from the Scopus database using keywords in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The results phase begins with an overview of the studies included with their respective authors and titles, as shown in Table 2. [11] Art in the Silence: New Experience Towards the Role of the Bilingual Hypoacous Teacher Chávez-Peña et al (2022) [12] Pedagogical leadership applied to teaching practice in times of pandemic crisis in Peru De Sa and De Carvalho (2020) [13] A proposal for technical-pedagogical support in professional and technological distance education courses Herrera-Pastor et al (2020) [14] Socio-pedagogical accompaniment, holism and longitudinality: Keys from a good practice with a young offender Kariyev et al (2022) [15] Development of primary school teachers' skills to accompany pupils in projects and research Karsenti et al (2020) [16] Digital technologies in teaching and learning foreign languages: Pedagogical strategies and teachers' professional competence Kenigs et al (2022) [17] Perception of teachers and school directors on teaching advice in the classroom Kozanitis et al (2018) [18] Continuous development and education follow-up of new university professors: Effects on the use of teaching strategies Lara-Reimundo et al (2022) [19] School management during the pandemic: relationship between educational support and teaching performance Marek and Walulik (2022) [20] Ignatian Spirituality as Inspiration for a Pedagogical Theory of Accompaniment Mojica and Palacios (2022) [21] Pedagogical strategy: Life plan for teenage mothers Morado and Hernandez (2019) [22] An Accompanying Experience in the Construction of Virtual Environments for Learning in Higher Education Navarro and Torres (2023) [23] Digital culture in the Telesecundaria school curriculum Neyra et al (2021) [24] Management of Pedagogical Supervision and Teacher Performance in the Teaching of English in Peru Pérez and Marquez (2022) [25] Pedagogical support in on-site and virtual professional practice Posso-Pacheco et al (2021) [26] Educational management: Key factor in the implementation of the physical education curriculum Rasskazova et al (2021) [27] Readiness of social services specialists for gender-sensitive activities with offence-prone juveniles Reyes and Azahuanche (2020) [4] Relationship between pedagogical accompaniment and reflective teaching practice Rosas et al (2022) [28] Pedagolical Support in, A Hybrid Setting, in Public Institutions and PRONOEI of the Initial Level…”
Section: Resultsmentioning
confidence: 99%
“…The results phase begins with an overview of the studies included with their respective authors and titles, as shown in Table 2. [11] Art in the Silence: New Experience Towards the Role of the Bilingual Hypoacous Teacher Chávez-Peña et al (2022) [12] Pedagogical leadership applied to teaching practice in times of pandemic crisis in Peru De Sa and De Carvalho (2020) [13] A proposal for technical-pedagogical support in professional and technological distance education courses Herrera-Pastor et al (2020) [14] Socio-pedagogical accompaniment, holism and longitudinality: Keys from a good practice with a young offender Kariyev et al (2022) [15] Development of primary school teachers' skills to accompany pupils in projects and research Karsenti et al (2020) [16] Digital technologies in teaching and learning foreign languages: Pedagogical strategies and teachers' professional competence Kenigs et al (2022) [17] Perception of teachers and school directors on teaching advice in the classroom Kozanitis et al (2018) [18] Continuous development and education follow-up of new university professors: Effects on the use of teaching strategies Lara-Reimundo et al (2022) [19] School management during the pandemic: relationship between educational support and teaching performance Marek and Walulik (2022) [20] Ignatian Spirituality as Inspiration for a Pedagogical Theory of Accompaniment Mojica and Palacios (2022) [21] Pedagogical strategy: Life plan for teenage mothers Morado and Hernandez (2019) [22] An Accompanying Experience in the Construction of Virtual Environments for Learning in Higher Education Navarro and Torres (2023) [23] Digital culture in the Telesecundaria school curriculum Neyra et al (2021) [24] Management of Pedagogical Supervision and Teacher Performance in the Teaching of English in Peru Pérez and Marquez (2022) [25] Pedagogical support in on-site and virtual professional practice Posso-Pacheco et al (2021) [26] Educational management: Key factor in the implementation of the physical education curriculum Rasskazova et al (2021) [27] Readiness of social services specialists for gender-sensitive activities with offence-prone juveniles Reyes and Azahuanche (2020) [4] Relationship between pedagogical accompaniment and reflective teaching practice Rosas et al (2022) [28] Pedagolical Support in, A Hybrid Setting, in Public Institutions and PRONOEI of the Initial Level…”
Section: Resultsmentioning
confidence: 99%